Cultural Content Analysis in the First Textbook of Arabiyyah Baina Yadaik: Cultural Content Analysis in the First Textbook of Arabiyyah Baina Yadaik - Rofida, Hilya; Fauji, Imam (Indonesian Journal of Education Methods Development, 2023)
This qualitative descriptive research examines the cultural content analysis within the inaugural volume of "Arabiyyah baina Yadaika." Employing the documenter method with primary and secondary sources, content analysis is employed to dissect the data. The study reveals the textbook's comprehensive integration of Islamic cultural concepts with linguistic structures, vocabulary, and authentic texts. Noteworthy are the inclusion of genuine Arabic linguistic examples, cultural landmarks, and maps, along with insights into Arab currencies. The initial Pelajaran segments introduce numerical concepts and underscore respect for Arab values and Arabic culture. Contemporary Arabic texts and discernible Islamic cultural trends further enrich the material. The study underscores the accuracy of the introduction to Arabic culture and its far-reaching implications for language education. Highlight: Comprehensive Fusion: The textbook seamlessly intertwines Islamic cultural concepts and linguistic structures, enhancing the learning experience. Authentic Illustration: Real-world examples, including Arabic names, landmarks, and currencies, provide practical context to language learning. Cultural Appreciation: The textbook's respect for Arab values and emphasis on Arabic culture contribute to a holistic language education approach. Keywords: Cultural content analysis, Arabic language textbook, Islamic culture, Content integration, Linguistic examples